Longitudinal Effects of Teriparatide or Zoledronic Acid on Bone Modeling‐ and Remodeling‐Based Formation in the SHOTZ Study. (23rd February 2018) - Dempster, David W; Zhou, Hua; Ruff, Valerie A; Melby, Thomas E; Alam, Jahangir; Taylor, Kathleen A
ABSTRACT: Previously, we reported on bone histomorphometry, biochemical markers, and bone mineral density distribution after 6 and 24 months of treatment with teriparatide (TPTD) or zoledronic acid (ZOL) in the SHOTZ study. The study included a 12‐month primary study period, with treatment (TPTD 20 μg/d by subcutaneous injection or ZOL 5 mg/yr by intravenous infusion) randomized and double‐blind until the month 6 biopsy (TPTD, n = 28; ZOL, n = 30 evaluable), then open‐label, with an optional 12‐month extension receiving the original treatment. A second biopsy (TPTD, n = 10; ZOL, n = 9) was collected from the contralateral side at month 24. Here we present data on remodeling‐based bone formation (RBF), modeling‐based bone formation (MBF), and overflow modeling‐based bone formation (oMBF, modeling overflow adjacent to RBF sites) in the cancellous, endocortical, and periosteal envelopes. RBF was significantly greater after TPTD versus ZOL in all envelopes at 6 and 24 months, except the periosteal envelope at 24 months. MBF was significantly greater with TPTD in all envelopes at 6 months but not at 24 months. oMBF was significantly greater at 6 months in the cancellous and endocortical envelopes with TPTD, with no significant differences at 24 months. At 6 months, total bone formation surface was also significantly greater in each envelope with TPTD treatment (all p < 0.001). For within‐group comparisons from 6 to 24 months, no statistically significant changes were observed in RBF, MBF, or oMBF in any envelope for either the TPTD or ZOL treatment groups. Overall, TPTD treatment was associated with greater bone formation than ZOL. Taken together the data support the view that ZOL is a traditional antiremodeling agent, wheareas TPTD is a proremodeling anabolic agent that increases bone formation, especially that associated with bone remodeling, including related overflow modeling, with substantial modeling‐based bone formation early in the course of treatment. © 2017 American Society for Bone and Mineral Research.